Effect of single infection of Plasmodium berghei and coinfection with Brugia pahangi in gerbils / Junaid Olawale Quazim - Junaid Olawale, Quazim (2018)
Malaria and lymphatic filariasis (LF) are two leading and common mosquito-borne parasitic diseases worldwide. These two diseases are co-endemic in many tropical and sub-tropical regions and are known to share vectors. The interactions between malaria and filaria parasites are poorly understood. Thus, this study aimed at establishing Plasmodium berghei ANKA (PbA) infection in gerbils and understanding its interactions with Brugia pahangi co-infections. Briefly, the gerbils were matched according to age, sex and weight and grouped into filaria-only infection, PbA-only infection, co-infection and control group. Filaria infection was established by inoculating 50 infective larvae of B. pahangi subcutaneously into each experimental gerbil. After a prepatent period of 70 days of B. pahangi infection, co-infection was initiated with the inoculation of 106 PbA infected red blood cells (iRBCs) intraperitoneally, whereas the PbA-only infected group of gerbils were initially given 0.2 mL phosphate buffered salt subcutaneously before being given 106 PbA iRBCs intraperitoneally after 70 days. The parasitaemia, survival and clinical effect on the gerbils were monitored for a period of 30 days post Plasmodium infection. The immune responses of gerbils to both mono and co-infection were monitored together with assessment of histopathology of the infections. Findings show that gerbils were susceptible to PbA infection, showing significant decrease in haemoglobin concentration, RBC counts, body weight and temperature, over the course of infection. However, there were no neurological signs observed and the death of gerbils might be as a result of severe anaemia. Results on co-infection experiments showed that co-infected gerbils survived longer than PbA-infected gerbils. Food and water consumption were significantly reduced in both PbA-infected and co-infected gerbils, although loss of body weight, hypothermia, splenomegaly and hepatomegaly were less iv severe in co-infected gerbils. Plasmodium infected gerbils also suffered hypoglycemia which was not observed in co-infected gerbils. Histopathology reveals that the presence of B. pahangi adults and microfilariae in the lungs of gerbil, invoked inflammatory responses and damages to the lungs in both filaria-only and co-infected gerbils. Furthermore, gerbil cytokine responses to co-infection were significantly higher than PbA-only infected gerbils, which is being suggested as a factor for their increase survivability. Co-infected gerbils had significantly elicited interleukin-4, interferongamma and tumour necrotic factor at early stage of infection than PbA infected gerbils. Findings from this study suggested that B. pahangi infection protected against severe anaemia, hypoglycemia, haemorrhagic alveolitis and bronchitis which are manifestations of PbA infection. Therefore, filaria infection seems to protect against severity of PbA infection in gerbils.